The US-India Strategic Partnership: Pakistan’s Foreign Policy Response - Riaz A. Khokhar (CISS Insight Journal, 2018)
The US-India strategic partnership is considered the watershed moment in the bilateral relationship between India and the United States1. It is underpinned by the historic civil-nuclear agreement as well as defence agreements for transfer of “high-end [military hardware]” 2 to India. Moreover, joint naval exercises of the US and India in the Indo-Pacific, including Indian demand for a liaison in the Arabian Sea, have potentially expanded India-Pakistan’s geostrategic competition from land to sea3. For Pakistan, the US’ civil nuclear deal distorted the uniform criteria governing the nuclear export control regime. Pakistan has proposed a criteriabased approach to civil-nuclear trade and the NSG membership. The growing transfer of advanced military technology and dual-use nuclear material to India has created strategic instability in South Asia’s volatile region. Therefore, in order to restore the strategic balance, Pakistan has taken a two-pronged approach. Besides further strengthening its ties with China, Pakistan is also expanding its defence relations and increasing cooperation in counterterrorism efforts with Russian Federation. Simultaneously, Pakistan has been working on its nuclear capability and adjusting its nuclear doctrine with a view to maintain its deterrence against India.